Pengaruh Intellectual Capital Dan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Perbankan - Widya Arviana Astuti (Akuntabel: Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine the effect of intellectual capital and good corporate governance on the financial performance of banking companies listed on the IDX for the 2018-2021 period. So that the research variables consist of 4 (four) independent variables, namely intellectual capital (X1), independent board of commissioners (X2), audit committee (X3). Institutional ownership (X4) and the dependent variable is Return on equity (Y). The population of this study are banking companies listed on the Indonesia Stock Exchange for the 2018-2021 period. Samples were taken using purposive sampling. The type of data used in this research is quantitative data. The data analysis method used in this study is a method of multiple linear regression statistical analysis. The results of this study indicate that Intellectual Capital (X1) has no significant effect on Company Performance proxied by Return on Equity, Independent Board of Commissioners (X2) has no significant effect on Company Performance proxied by Return on Equity, Audit Committee (X3) has no significant effect on Company Performance proxied by Return on Equity, and Independent Ownership (X4) has no significant effect on Company Performance proxied by Return on Equity. The results of this study also show that the independent variables (Intellectual Capital, Independent Board of Commissioners, Audit Committee, and Independent Ownership) are 0.6%. While the remaining 99.4% the quality of financial performance is influenced by other variables.